The role of educational supervisors in developing the first teachers’ job performance in the light of the goal supervision model at the governorate of muscat schools: a first supervisor’s perspectives - Alhadidi1, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya (OCERINT International Organization Center of Academic Research, 2020)
This qualitative study discussed the first educational supervisors’ perspectives in developing the job performance of the first teachers, due to the objective’s supervision model at Muscat Governorate schools. The statement problem was the absence of the educational supervisors’ role in the developing of the first teachers’ performance, and the weakness of goals supervision application. The objective of the study: to discuss the role of educational supervisors in developing the first teachers’ job performance in the light of supervision model, the study adopted the descriptive qualitative approach, using the interviews for data collection. The study sample were (4) supervisors at the General Directorate of Education in Muscat. The findings revealed that; the role of educational supervisors in developing the job performance of the first teachers was high of the goal supervision model; On the existence of a (high) estimate in the fields of (implementation, field follow-up, and evaluation), and on a (average) to relatively low estimate in the areas of (goals, planning) in some of the goals and plans.